2019
DOI: 10.3390/en12193688
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Evolution at Various Pressure Gradients in Natural Gas Hydrate Reservoir at the Shenhu Area in the South China Sea

Abstract: The sediment of the hydrate reservoir in the Shenhu Area is mainly clayey silt. Its characteristic small particles and poor cementation challenge the quantification of the reservoir permeability during gas production. An accurate description of the seepage mechanism of the clayey-silt reservoir is the basis, and also a difficulty, of effective development of gas in the South China Sea. In this study, four sets of water seepage experiments under different pressure gradients are carried out using the clayey-silt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Yu and Cheng [22] established the fractal permeability model for the bidispersed porous media and introduced the algorithm of pore space fractal dimension and tortuosity fractal dimension based on the box-counting method. Cai et al [23] established a fractal permeability model for creeping microstructures under different pressure conditions based on the data of water flooding experiment combined with CT scanning [24] for clayey silt sediments. Liu et al [25] used fractal dimensions to establish a fractal theory-based relative permeability model of hydrate-bearing sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Yu and Cheng [22] established the fractal permeability model for the bidispersed porous media and introduced the algorithm of pore space fractal dimension and tortuosity fractal dimension based on the box-counting method. Cai et al [23] established a fractal permeability model for creeping microstructures under different pressure conditions based on the data of water flooding experiment combined with CT scanning [24] for clayey silt sediments. Liu et al [25] used fractal dimensions to establish a fractal theory-based relative permeability model of hydrate-bearing sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Clay and quartz are dominant, which account for 47.2% and 36.4%, respectively. The clay minerals are mainly montmorillonite and illite [19,37].…”
Section: Samples and Experiments Methodsmentioning
confidence: 99%
“…The formation energy depletes at the later stage of hydrate gas production, causing the decline in thermal and pressure conductivity of the reservoir, which is difficult to spread to the far end of the wellbore [33][34][35]. Meanwhile, lack of gas channel to flow 3 Geofluids from the dissociation front to the wellbore, the gas production is seriously affected [36][37][38][39]. Therefore, the fracture propagation characteristics of clayey-silt sediments in hydrate dissociation are an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…In the early experiment of water flow in the clay-silt sediment core from the South China Sea, it is found that the permeability decreased gradually with the increase in differential pressure and this process is irreversible [18]. CT scanning was used to observe the phenomenon of pore volume creep in the sample during the flow process, and there was a clear power law relationship between the effective permeability and porosity of sediments under different pressure differences.…”
Section: Introductionmentioning
confidence: 99%